Profesionalisme Hakim Peradilan Agama Dalam Penerapan Prinsip I’tibar: Tinjauan Fiqh Dan Hukum Acara Peradilan Agama - Deryasa Deryasa; Taufiq Alamsyah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
A judge’s decision is expected to reflect three essential elements: justice, legal certainty, and benefit. In practice, however, judges often encounter cases not explicitly regulated by existing laws, which requires ijtihad through the principle of i’tibar evaluating cases from the perspective of substantive justice and truth. This study aims to explore the concept of i’tibar as an indicator of judicial professionalism in adjudicating cases, as well as its relevance in both fiqh and procedural law of religious courts. The research adopts a qualitative method with a library research approach, drawing on primary and secondary sources such as books, scholarly articles, and legal regulations. The findings show that the principle of i’tibar can serve as a valuable foundation for judicial reasoning without disregarding the positive law in Indonesia. In this way, i’tibar strengthens the professionalism of judges in realizing substantive justice.